Zur Frage des Anwachsens von ganzen transzendenten Lösungen partieller Differentialgleichungen - Strelits, S. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш. И. Стрелиц. К вопросу о росте целых трансцендентных решений уравнений в частных производныхS. Strelicas. Dalinių diferencialinių lygčių sveikų transcendentinių sprendinių augimo klausimu